Pengaruh Variasi Penambahan Pome Terhadap Rasio C/N Pada Pengomposan Tks Sisa Media Tanam Jamur Merang - Naomi Ebinasari BR Sembiring; Elvi Yenie; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Composting is one of the best methods for handling empty fruit bunch (EFB) waste. This research aims to learn effect variation of additions Palm Oil Mill Effluent (POME) in composting process of EFB spent paddy straw mushroom (Volvariella volvacea) toward C/N ratio. Palm Oil Mill Effluent (POME) was added gradually (in day 0, 7th, and 14th) and variation of substrate mixture (EFB spent paddy straw mushroom : POME) are 1:0; 1:1; 1:2; and 1:3. The result shows the composting process finish in the day 7th (faster than research estimate, with 1 time POME addition) and the best variation of substrate mixture is (D) (1:3). The mature compost has C/N ratio 13,07. Key words : EFB spent paddy straw mushroom, C/N ratio, Composting, POME